Analysis of Retrospective Time to First Pregnancy Data in Uttar Pradesh under Various Dimensions - Maheshwari, Sonam; Singh, Brijesh P.; Pudir, P.S. (Journal of Institute of Science and Technology, 2015)
The present study deals with the estimation of the mean value of fecundability by fitting a theoretical distribution from the observed distribution of first conception of the women, who did not use any contraceptive method before their first conception. It is assumed that fecundability is fixed for a given couple, but across couples it varies according to a specified distribution. Under the classical approach, methods of moment and maximum likelihood are used while for Bayesian approach, empirical Bayes method used. A real data analysis from the third National Family Health Survey (NFHS-III, 2005-06) is analyzed as an application of model for various age at marriage groups of women. Finally, a simulation study is performed to access the performance of the several of methods used in this paper. Journal of Institute of Science and Technology, 2015, 20(1): 51-58